Biophysical controls on spatial and summer/winter distributions of total and chromophoric dissolved organic matter in the Taiwan Strait - Hung, Jia-Jang; Lu, Wan-Tzu; Yang, Hsin-Mei; Lin, Yen-Hui; Guo, Laodong (Frontiers in Marine Science, 2022)
This study examined the physical and biogeochemical processes that determine the spatial and summer/winter distributions of dissolved organic matter (DOM) and chromophoric dissolved organic matter (CDOM) in the Taiwan Strait (TS). The hydrological conditions in the TS varied between early summer and winter because of differences in terrestrial input as well as input from the poleward South China Sea Water (SCSW) during the warm summer and the strong, nutrient-rich, equatorward China Coastal Water (CCW) in winter. The distributions Concentrations of dissolved organic carbon (DOC) ranged from 60 to 100 μM-C in early summer and from 70 to 144 μM-C in winter. The average stoichiometric ratio of DOC:DON:DOP was high (353:49:1) in the land-source impacted zones and low (168:21:1) in the SCSW-laden areas, both of which are higher than the Redfield ratio. The concentrations of DOC and nutrients were higher in the western TS (on the coast of China) than in the eastern TS (on the coast of Taiwan), and the highest concentrations were mostly found in the Minjiang River plume, reflecting the profound effects of freshwater input in early summer and CCW inflow in winter. The absorption and emission characteristics of the CDOM varied to a large extent with locations because of the mixing of the shelf water with different source waters. Although the absorption coefficient (aCDOM(325)) and fluorescence intensity of the terrestrial humic-like CDOM (Ft: Ex/Em= 260/400-460) were both strongly inversely correlated with salinity, as an optical tracer, Ft may be more effective than aCDOM(325) as an optical tracer ofin examining the mixing among source waters, given that aCDOM(325) may be subject to various photobleaching effects in the TS. Ft was also significantly correlated with the concentrations of terrestrially derived nitrate and nitrite (N+N) and silicate. The factor analysis elucidated the complexity of the hydrological and biological processes that affect the distributions of DOM and CDOM in the TS.